2004
DOI: 10.1075/ni.14.1.04han
|View full text |Cite
|
Sign up to set email alerts
|

A model of narrative circulation

Abstract: This article suggests that narrative meaning structures have different modes of existence: the “told”, the “inner” and the “lived” modes. Their definitions and mutual relationships are presented in the form of a schematic model. The inner narrative represents the experiental mode of narrative form. It is an individual's interpretation of his/her life, in which the past events, present situation and future projects are understood using cultural narrative models as resources. It is (partly) made external by told… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0
13

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 38 publications
0
64
0
13
Order By: Relevance
“…The teachers found that in the interviews they had an opportunity to make sense and understand the reform, to talk about their concerns and to elaborate the influences of the reform for the future 29 (Hänninen 2004;Sfard and Prusak 2005;Taylor and Littleton 2006). For many teachers, the interview was in fact their first opportunity to discuss the reform, since the lack of time had restricted opportunities for making sense of the reform, either individually or collectively.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The teachers found that in the interviews they had an opportunity to make sense and understand the reform, to talk about their concerns and to elaborate the influences of the reform for the future 29 (Hänninen 2004;Sfard and Prusak 2005;Taylor and Littleton 2006). For many teachers, the interview was in fact their first opportunity to discuss the reform, since the lack of time had restricted opportunities for making sense of the reform, either individually or collectively.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The construction of narratives is particularly important for individuals within situations of change: it helps the narrator to gain a sense of coherence, continuity and stability of the self (Ellis and Bochner 2000;Hänninen 2004). Narrating makes us able to cope with new situations in terms of our past experiences, and it gives us tools to plan for the future (Sfard and Prusak 2005).…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, postmodern theory describes contemporary narratives as "smallish" and "localized" (Ritzer, 2008, p. 618). But, as Hänninen (2004) argues, while the concept of "relative freedom" contains divergent and localized narratives, "on the community and group level, however, the options are often much more restricted in terms of what kinds of narrative interpretations are considered appropriate or suitable" (Hän-ninen, 2004, p. 77). In this study, we prefer the concept of metanarrative: it underlines the meta-level character and cultural dominance of particular narratives, and it has recognized status in sociological discourse.…”
Section: Eerola and Huttunenmentioning
confidence: 99%
“…However, in narrative inquiry, numerous concepts of dominant narratives exist. These narratives are present in our society as commonly known "truths"; these include such concepts as metanarrative, public narrative, master narrative, dominant stories and cultural stock of stories (e.g., Hänninen, 2004;Sommers, 1994). In societal and cultural discourses, these narratives are widely spread, frequently told and rarely questioned.…”
Section: Eerola and Huttunenmentioning
confidence: 99%